2021
DOI: 10.1167/iovs.62.13.7
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Derived Proteases Contribute to the Pathogenesis of Early Diabetic Retinopathy

Abstract: Purpose Previous studies indicate that leukocytes, notably neutrophils, play a causal role in the capillary degeneration observed in diabetic retinopathy (DR), however, the mechanism by which they cause such degeneration is unknown. Neutrophil elastase (NE) is a protease released by neutrophils which participates in a variety of inflammatory diseases. In the present work, we investigated the potential involvement of NE in the development of early DR. Methods Experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 62 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…Patients with DR and animal models have been shown to exhibit a variety of inflammation-related characteristics, including tissue edema, enhanced vascular permeability, elevated blood flow, up-modulation of cytokines, activation of complement and microglial, infiltration of neutrophils and macrophages, and leukostasis. [34][35][36] Notably, the elevation in these inflammatory factors that are produced by microglia, endothelial cells, macroglia, and later even neurons indicates dramatic increases in the activities of these inflammatory markers in the early stage of DR and the progression of inflammation across all the cell types of the retina. 37,38 Some of the cytokines identified, such as interleukin (IL)-1, IL-3, and monocyte chemoattractant protein-1 (MCP-1) are reported to be involved in angiogenesis, as demonstrated in experimental ischemic mouse models demonstrating that inflammatory responses lead to and predate the progression of neovascularization in proliferative DR. 39,40 Moreover, it has been proven that blocking or deleting pro-inflammatory markers can inhibit the progression of diabetes-elicited vascular and neuronal pathology in animal models of the DR. 41,42 According to the aforementioned results, we hypothesized that NPAR, the blending of albumin and neutrophils, has a high prognostic significance in the progression of DR. NPAR is simplistic, inexpensive, and rapid, which makes it a potential indicator that may be used even in undeveloped medical areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with DR and animal models have been shown to exhibit a variety of inflammation-related characteristics, including tissue edema, enhanced vascular permeability, elevated blood flow, up-modulation of cytokines, activation of complement and microglial, infiltration of neutrophils and macrophages, and leukostasis. [34][35][36] Notably, the elevation in these inflammatory factors that are produced by microglia, endothelial cells, macroglia, and later even neurons indicates dramatic increases in the activities of these inflammatory markers in the early stage of DR and the progression of inflammation across all the cell types of the retina. 37,38 Some of the cytokines identified, such as interleukin (IL)-1, IL-3, and monocyte chemoattractant protein-1 (MCP-1) are reported to be involved in angiogenesis, as demonstrated in experimental ischemic mouse models demonstrating that inflammatory responses lead to and predate the progression of neovascularization in proliferative DR. 39,40 Moreover, it has been proven that blocking or deleting pro-inflammatory markers can inhibit the progression of diabetes-elicited vascular and neuronal pathology in animal models of the DR. 41,42 According to the aforementioned results, we hypothesized that NPAR, the blending of albumin and neutrophils, has a high prognostic significance in the progression of DR. NPAR is simplistic, inexpensive, and rapid, which makes it a potential indicator that may be used even in undeveloped medical areas.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DR and animal models have been shown to exhibit a variety of inflammation‐related characteristics, including tissue edema, enhanced vascular permeability, elevated blood flow, up‐modulation of cytokines, activation of complement and microglial, infiltration of neutrophils and macrophages, and leukostasis 34–36 . Notably, the elevation in these inflammatory factors that are produced by microglia, endothelial cells, macroglia, and later even neurons indicates dramatic increases in the activities of these inflammatory markers in the early stage of DR and the progression of inflammation across all the cell types of the retina 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…The classical visual cycle is essential to sustain phototransduction over time; however, compelling data indicate that this pathway can also drive disease progression in specific retinopathies including Stargardt disease (STGD), diabetic retinopathy (DR), light-induced retinopathy, and potentially age-related macular degeneration (AMD). , Indeed, genetic ablation of essential enzymes , and retinoid-binding proteins of the visual cycle, or their inhibition, protects the retina from degeneration induced by light.…”
Section: Introductionmentioning
confidence: 99%
“…Leukostasis is strongly implicated in retinal EC apoptosis that gradually leads to retinal vascular degeneration, a major clinically recognized lesion of early DR (11). Since we found that LOX-dependent vascular stiffening promotes retinal leukostasis in short-term diabetic mice, we asked whether LOX could thereby mechanically induce retinal EC apoptosis and vascular degeneration following prolonged diabetes (20-30 weeks duration).…”
Section: Resultsmentioning
confidence: 99%
“…Alteration in vascular/EC stiffness regulates EC fate by modifying its susceptibility to soluble factors (2, 12). Thus, we asked whether increased retinal vascular/EC stiffness in diabetes promotes EC apoptosis by increasing cell susceptibility to neutrophil elastase, a serine protease that is strongly implicated in neutrophil-induced retinal EC apoptosis (11). Indeed, neutrophil elastase treatment of HRECs grown on the stiff matrix, which mimics retinal vascular stiffness in diabetic mice, led to a 1.5-fold increase (with reference to/w.r.t normal matrix; p<0.01) in caspase-3 activation (Fig.…”
Section: Resultsmentioning
confidence: 99%